Numerical Simulation of Thermal Processes and Influence of Heating Surface Layers of Silicon on the Titanium Accumulation and Diffusion During High-Intensity Pulse Ion Implantation; Energy Fluxes and Radiation Effects (EFRE-2024) - Ivanova A. I. Anna Ivanovna (2024, 2024)
Текстовый файл